An investigation into factors that contribute to the perception of disparities between academic achievement and athletic participation in high school student-athletes - Rowles, K. S. (The Sport Journal, 2015)
The purpose of this study was to analyze and compare various factors that contribute to the attitudes and perceptions held by public high school student- athletes towards academic achievement. During the 2014-2015 academic year, 323 student-athletes completed a 110 question survey packet that included, the Non Cognitive Questionnaire (NCQ), the Athletic Identity Measure Scale (AIMS), the Student Athletic Motivation Survey and Questionnaire (SAMSAQ), the Student-Athlete Role Conflict Scale and the Sport Commitment Model (SCM), providing information about different aspects of the academic achievement and athletic participation relationship, including level of educational aspirations and academic self-concept, the internal struggle between the student and athlete identity complexes, and motivational drives of student-athletes. Student Participation was strictly voluntary and contingent upon the willingness of coaches and parental consent. Student-athletes generally viewed themselves as student-athletes and believed it is worth the effort to achieve athletic success but not at the expense of their academic performance. Analysis showed that gender may play a statistically significant role in student-athletes` perception of academic performance and athletic participation while grade level, age and race were less meaningful. The researcher hopes these findings may encourage further research, and potentially aid parents, coaches, counselors and teachers in assisting student athletes with maintaining a balance between academics and athletics.